Postharvest quality changes of salvia (Salvia officinalis) stored under cold-storage conditions - Romero Tejeda, María de la Luz; Martínez Damián, María Teresa; Rodríguez Pérez, Juan Enrique; Colinas León, María Teresa Beryl; Martínez Solís, Juan (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The aim of this study was to evaluate the effect of low temperatures on the postharvest quality of sage (Salvia officinalis L.). For this, the plants were stored at 0º to 6ºC with compared to 23 Â± 2ºC (control) and packed in polyethylene bags, low density for 21 days. During this period were evaluated every three days: respiration rate (TR), production of ethylene (PE), weight loss (WL), total soluble solids (TSS), titratable acidity (TA), the total chlorophyll (CLT), color (*L, *C, ºh) and vitamin C (VtC). Additionally, through a sensory evaluation: visual appearance, color scale, yellowing, leaf abscission and decay. The use of cooling (0º to 6ºC) maintained the TR and PE values were 15.4 to 22.9 mL CO2Â·kg-1 Â· h-1 and 0.06 to 0.46mL ethylene Â· kg-1 Â· h-1, respectively. The use of cooling diminished WL up to 40% sage. The CT and CL were stored for up to 15 days to 6ºC. The VtC gradually decreased, but this decrease were more evident in the treatment at 23ºC. The best treatment was 0ºC, since, allowed prolong the quality of sage up to 12 days, contrary to the treatments to 6º and 23ºC where quality only maintained for up to 9 and 6 days, respectively.